Analisis Pengaruh Disiplin dan Lingkungan Kerja terhadap Kepuasan Kerja Pegawai Dinas Sumber Daya Air, Bina Marga, dan Bina Konstruksi Kabupaten Kepulauan Tanimbar - Nusmese, Fransiskus; Man’na, Petrus; jaya, Amir (Journal of Comprehensive Science, 2025)
Human resources, in this case employees, are a central factor in an organization or company. The success of an organization is determined by employee performance, and one of the indicators to improve employee performance is having high job satisfaction. To achieve high job satisfaction, there needs to be motivating factors such as discipline and a conducive work environment. The purpose of this research is to: determine the partial effect of discipline on job satisfaction, identify the partial effect of the work environment on employee job satisfaction, and assess the simultaneous effect of discipline and the work environment on employee job satisfaction at the Water Resources, Bina Marga, and Construction Agency of Tanimbar Islands Regency. This type of research is qualitative. The location and population for this study consist of 15 employees and contract workers at the Water Resources, Bina Marga, and Construction Agency of Tanimbar Islands Regency. The data sources for this research are primary and secondary data. Data collection methods include interviews, observations, and documentation. The data analysis method follows Miles and Huberman’s approach, which is a qualitative data analysis conducted interactively and continuously until completion, starting from data reduction, data presentation, and drawing conclusions. The research results indicate that work discipline and the work environment have a simultaneous effect on job satisfaction among employees at the Water Resources, Bina Marga, and Construction Agency of Tanimbar Islands Regency.